The Bonnor-Melvin magnetic 2+1+p-brane solution in gravity coupled to nonlinear electrodynamics - Mazharimousavi, S. Habib (Iop Publishing Ltd, 2023)
In this work, we present a 2 + 1 + p-brane solution in Einstein's gravity coupled to the nonlinear electrodynamic with the Lagrangian density-root F-mu nu F-mu nu powered by a true uniform magnetic field. The three and four-dimensional solutions coincide with the recently reported Bonnor-Melvin universe with a cosmological constant in gravity coupled with Maxwell's linear Lagrangian in [50] and [7], respectively. The magnetic fields are produced by electric currents through coil-type wires located periodically with the discreet radii. The invariants of the spacetime are regular/constant everywhere but nonzero and proportional to Maxwell's invariant.
Keywords: Bonnor-Melvin; nonlinear electrodynamics; brane solution; regular spacetime; magnetic universe